Prevalence of coronary heart disease (by epidemiological criteria) and its association with lipid and non-lipid risk factors in the Novosibirsk population of 25-45 years - Yu. I. Ragino; N. A. Kuzminykh; L. V. Shcherbakova; D. V. Denisova; V. S. Shramko; M. I. Voevoda (Российский кардиологический журнал, 2019)
Aim. To study the prevalence of coronary artery disease (CAD) according to epidemiological criteria in the Novosibirsk population of 25-45 years, to identify its associations with lipid and non-lipid risk factors.Material and methods. Cross-sectional survey of the Novosibirsk population aged 25-45 was carried out. The study included 650 people (268 men and 382 women). The epidemiological diagnosis of CAD (“Certain CAD” — CCAD, “Possible CHD” — PCAD) was made according to epidemiological (according to Rose questionnaire) and clinical functional (ECG recording with the Minnesota code) criteria. Blood levels of total cholesterol, triglycerides, cholesterol of low and high density lipoproteins (LDL-Ch, HDL-Ch) were determined. Blood pressure were measured (SBP, DBP), the presence of arterial hypertension (AH), body mass index and the smoking status were assessed.Results. CCAD was detected in 3,8% people, including in 2,6% men and in 4,7% women. PCAD was detected in 6,1% people, including 78% men and 5,0% women. The results of univariate analysis showed that the relative risk of PCAD in the population is higher in people with low HDL-Ch (OR 2,136), in smokers (OR 1,925) and in AH subjects (OR 2,235). The results of logistic regression analysis showed that the relative risk of PCHD in the population, independently of other factors, is associated with lower level of HDL-Ch (OR 0,180) and higher SBP (OR 1,026). The relative risk of CCAD developing in the female population is higher in women with low HDL-Ch (OR 3,800) and in AH women (OR 4,572).Conclusion. In the Novosibirsk population of 25-45 years, CAD, determined by epidemiological criteria, independently of lipid and non-lipid risk factors, is associated with AH presence and reduced HDL-Ch.